Carbohydrate-based adjuvants activate tumor-specific Th1 and CD8+ T-cell responses and reduce the immunosuppressive activity of MDSCs. (January 2019) - Xu, Xiaojing; Jin, Ziqi; Liu, Yonghao; Gong, Huanle; Sun, Qing; Zhang, Weidong; Zhao, Lixiang
Abstract: Toll-like receptors (TLRs) and C-type lectin receptors (CLRs) contribute to antigen capture, uptake, presentation and activation of immune responses. We recently developed a new and lymph node (LN) targeting adjuvant (D-CpG) by chemical conjugation type B CpG DNA with FDA-approved dextran polymer for lymph node imaging. To elucidate the possible antitumor mechanisms of this adjuvant, prophylaxis and therapeutic models of melanoma were used in this study. Our results showed that D-CpG was an efficient adjuvant of protein-based tumor vaccine in both prophylaxis and therapeutic models. It enhanced the tumor-specific Th1 and CTL responses. It also facilitated the tumor infiltration of the T cells and promoted IFNγ and TNFα production of both CD4 + and CD8 + T cells. In therapeutic model, D-CpG included tumor vaccine decreased the percentage of CD11b + Gr1 low+ MDSCs in spleen and inhibited their infiltration in tumor microenvironments. Administration of the D-CpG included vaccine significantly inhibited lung metastasis of the tumor through similar mechanisms. In conclusion, D-CpG used as tumor vaccine adjuvant can enhance both Th1 and CTL responses and inhibit CD11b + Gr1 low MDSCs, which may have general applicability to the development of vaccines against tumors. Highlights: Chemical conjugation CpG DNA with dextran polymer (D-CpG) enhances antitumor activities. D-CpG promotes both tumor-specific Th1 and Tc1 responses. D-CpG supresses CD11b + Gr1 low MDSCs.